Tradisi Walimah Pernikahan Masyarakat Cengkareng Barat - Jessika Jessika; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The wedding walimah is a religious tradition that has strong roots in Islamic teachings and continues to thrive in social practices. In the West Cengkareng area, the walimah tradition is not only understood as an expression of gratitude for the marriage contract, but also as a means of strengthening social solidarity and maintaining relationships. This study aims to analyze the wedding walimah tradition of the Cengkareng Barat community from the perspective of living hadith, which is to see how the Prophet's hadith is understood and manifested in the context of local culture. This study uses a qualitative method with a phenomenological approach through observation, interviews, and documentation. The results of the study show that the practice of walimah is based on the hadith of the Prophet Muhammad, which encourages the holding of walimah, even if it is simple. In practice, walimah has undergone local cultural acculturation, both in terms of the form of the banquet and the series of events. This study concludes that the tradition of wedding walimah in West Cengkareng is a form of hadith that is alive and dynamic in the community.